2003
DOI: 10.1055/s-2003-43223
|View full text |Cite
|
Sign up to set email alerts
|

Iridoid Glucosides from the Flowers ofBarleria lupulina

Abstract: A new iridoid diglucoside, lupulinoside, and eight known iridoid glucosides, acetylbarlerin, ipolamiidoside ( 3), 6-O-acetylshanzhiside methyl ester, barlerin, shanzhiside methyl ester, mussaenosidic acid, 8-O-acetylshanzhiside, and shanzhiside have been isolated from the flowers of Barleria lupulina. The structure of the new compound was established as 8-O-acetyl-2'- O-(beta-glucopyranosyl)mussaenoside by spectroscopic, especially 2D NMR, techniques. When tested for anti-herpes simplex type 1 activity, only c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…Thus, HAE-BL selectively activates Nrf2-mediated transcription. In contrast, we did not detect induction of Nrf2 target genes with two compounds previously isolated from Barleria lupulina and which we specifically identified in HAE-BL: the iridoid glycoside, shanzhiside methyl ester (Kanchanapoom et al, 2001; Kim et al, 2015; Suksamrarn et al, 2003), and the phenolic glycoside, poliumoside (Kanchanapoom et al, 2001) (Figure 1A). We also investigated induction of Nrf2 target genes by HAE-BL at 4 hours.…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…Thus, HAE-BL selectively activates Nrf2-mediated transcription. In contrast, we did not detect induction of Nrf2 target genes with two compounds previously isolated from Barleria lupulina and which we specifically identified in HAE-BL: the iridoid glycoside, shanzhiside methyl ester (Kanchanapoom et al, 2001; Kim et al, 2015; Suksamrarn et al, 2003), and the phenolic glycoside, poliumoside (Kanchanapoom et al, 2001) (Figure 1A). We also investigated induction of Nrf2 target genes by HAE-BL at 4 hours.…”
Section: Resultscontrasting
confidence: 71%
“…In particular, the Thailand Ministry of Public Health has categorized BL as an essential medicinal plant for primary healthcare (Wanikiat et al, 2008). Phytochemical studies on this plant have focused on a number of iridoid glycosids as main components (Kanchanapoom et al, 2001; Kim et al, 2015; Suksamrarn et al, 2003). However, the compounds in BL that provide medicinal benefits towards reducing inflammation and the vascular complications of diabetes have not been defined.…”
Section: Introductionmentioning
confidence: 99%
“…Several chemical constituents have been identified through GC-MS analysis of the ethanolic extract (Table 3). Some compounds viz., phenol,2,4,bis (1,1-dimethylethyl)-tetradecanoic acid, 12-methyl-, methyl ester, hexadecanoic acid, methyl ester, phytol and octadecanoic acid have also been reported by Omulokoli et al [22] and Namuli et al [23]. Cyclobutane, 1,1-dimethyl-2-octyl, 2-hexyl-1-octanol, 1, 2-henzenedicarboxylic acid, mono (2-ethylhexyl) ester and 1-hentetracontanol have been reported in essential oil of B. lupulina by Sarmad et al [24].…”
Section: Discussionmentioning
confidence: 83%
“…It comprises of several medicinal properties including antibacterial and anti-inflammatory activities [ 15 ], anticancerous [ 33 ], anti-HSV-2 activities [ 35 , 36 ], anti-clastogenic, anti-tumor [ 28 , 29 ], antiarthritic [ 15 ], anti-diabetic, immunomodulatory [ 17 ]. Suksamrarn et al [ 27 ] reported that several iridoid glucosides, bataine and alkaloids have also been reported from B. lupulina plant. Traditionally, leaves of this plant are used to treat snake bites, dog bites, swelling, bleeding wounds and rheumatism.…”
Section: Introductionmentioning
confidence: 99%